UPAYA MENINGKATKAN PRESTASI BELAJAR IPA DENGAN METODE PEMBELAJARAN PENEMUAN (DISCOVERY) - Rasmi Rasmi (LPPM UNISDA, 2018)
The purpose of this action research is to find out: (1) the improvement of student learning achievement after the implementation of discovery learning and (2) the influence of student learning motivation after the implementation of discovery learning method. This study uses action research as many as three rounds. Each round consists of four stages: design, activity and observation, reflection and refinement. The subject of this study was the sixth grade students of the Gas Semester Blimbing II Elementary School, Paciran Subdistrict, Lamongan Regency, 2015/2016 Academic Year. Data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the data analysis concluded that student achievement has increased from cycle I to cycle III, namely, cycle I (58.33%), cycle II (75%), cycle III (91.33%).